Manufacturing approaches to making muffins of high nutritional value - Samokhvalova, Olga; Kucheruk, Zinoviya; Kasabova, Kateryna; Oliinyk, Svitlana; Shmatchenko, Nataliа (Technology audit and production reserves, 2020)
The object of this study is the technology of baking muffins using beetroot fibers and wheat germ meal. Muffins are popular flour-based confectionery products with pleasant physical appearance and a variety of flavors, which are characterized by high energy and low food values. In addition, they are most often prepared using polycomposite mixtures, which does not make it possible to obtain products with a physiologically significant content of biologically active substances. It has been proposed while improving the technology of making muffins of high nutritional value to use such products of wheat germ and beet pulp processing as the additives «Beet fibers» and «Wheat germ meal» to serve the sources of physiologically functional ingredients. Beetroot fibers contain in their composition pectin-cellulose-hemicellulose complex of non-starch polysaccharides, polyphenolic compounds, and minerals (magnesium, calcium, sodium, etc.). The chemical composition of wheat germ meal is represented by a cellulose-hemicellulose complex, quite high content of vitamin E, polyphenolic compounds, and a significant amount of potassium, phosphorus, magnesium, calcium. The influence of wheat germ and beet pulp processing products has been investigated when partially replacing wheat flour, 25.0‒75.0 % and 10.0‒20.0 %, respectively. The formulation composition of muffins was optimized resulting in the substantiation of the amount of experimental additives (15.0 %, beet fibers; 50.0 %, wheat germ meal) and a decrease in the formulation content of sugar by 30.0 %. The organoleptic and physicochemical indicators of muffins have been determined, as well as the amount of physiologically functional ingredients in the products containing wheat germ and beet pulp processing products. The functional- technological scheme of muffin production has been built involving the addition of beet fibers and wheat germ meal. The improved muffin technology differs from conventional technologies by the application of natural raw materials, lack of food additives of synthetic origin, and the introduction of beet fibers and wheat germ meal, which makes it possible to make products with high nutritional value while maintaining the appropriate quality.